Reconstructing 'True Convivencia': The Roles of Muwalladun Mozarab and Jews in Coexistence in Al-Andalus During the Golden Age of Umayyad and First Taifa Periods - Mohammad Nor Bin Zaidi (Tunas Harapan Ummat Foundation, 2025)
This article investigates the unique interaction between three social groups; Muwalladun, Mozarabs and Jews, that lived together during Muslim Spain's era (732 CE-1492 CE) with the focus on unravelling the socio-cultural mechanism behind this interaction which led to the culmination of an interesting period known as